Chromosome-level genome assembly of Dongxiang wild rice (Oryza rufipogon) provides insights into resistance to disease and freezing - Que, Zhiqun; Lu, Qineng; Shen, Chunxiu (Frontiers in Genetics, 2022)
Dongxiang wild rice (DXWR, Oryza rufipogon Griff.) belongs to common wild rice Oryza rufipogon, which is the well-known ancestral progenitor of cultivated rice, possessing important gene resources for rice breeding. However, the distribution of DXWR is decreasing rapidly, and no reference genome has been published to date. In this study, we constructed a chromosome-level reference genome of DXWR by Oxford Nanopore Technology (ONT) and High-through chromosome conformation capture (Hi-C). A total of 58.41 Gb clean data from ONT were de novo assembled into 231 contigs with the total length of 413.46 Mb and N50 length of 5.18 Mb. These contigs were clustered and ordered into 12 pseudo-chromosomes covering about 97.39% assembly with Hi-C data, with a scaffold N50 length of 33.47Mb. Moreover, 54.10% of the genome sequences were identified as repeat sequences. 33,862 (94.21%) genes were functionally annotated from a total of predicted 35,942 protein-coding sequences. Compared with other species of Oryza genus, the genes related to disease and cold resistance in DXWR had undergone a large-scale expansion, which may be one of the reasons for the stronger disease resistance and cold resistance of DXWR. Comparative transcriptome analysis also determined a list of differentially expressed genes under normal and cold treatment, which supported DXWR as a cold-tolerant variety. The collinearity between DXWR and cultivated rice was high, but there were still some significant structural variations, including a specific inversion on chromosome 11, which may be related to the differentiation of DXWR. The high-quality chromosome-level reference genome of DXWR assembled in this study will become a valuable resource for rice molecular breeding and genetic research in the future.